PENGARUH KOMPOS JERAMI PADI DAN PUPUK NPK TER HADAP PERTUMBUHAN DAN PRODUKSI BAWANG MERAH (Allium ascalonicum L.) - Septi Sahtayani Tarigan; Hapsoh Hapsoh; Sri Yoseva (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The purpose of this research is to find out the effect of rice straw compost, NPK fertilizer and interaction rice straw compost and NPK fertilizer to find the best dosage for growth dan production of onions. This research was conducted in the experimental field Faculty of Agriculture, University of Riau in Campus Binawidya Km 12.5 Simpang Baru Panam, Pekanbaru. This research was conducted from February 2016 to Mei 2016. The research used Completely Randomized Design (CRD) with two factors. First factor is rice straw compost (P) which 3 levels, they are P1 = 600 g/1,2 m2 ; P2 = 1200 g/1,2 m2 and P3=1800 g/1,2 m. Second factor is NPK fertilizer (N) which 3 levels, they are N1=12 g/1,2 m2, N2=24 g/1,2 m2 dan N3= 36 g/1,2 m2. The combination of these two factors become 9 treatments and with 3 replications so there are 27 experimental units. Parameters observed are plant height, number of tubers, diameter of tubers, fresh weight tubers and dry weight tubers. The research used Analysis of Variance and further by Multiple Range Test Duncan’s at 5% level. The result concluded that treatment of rice straw compost 1800 g/1,2 m2 and NPK fertilizer 24 g/1,2 m2 may be recomanded for growth and production onions. Keywords : Allium ascalonicum L., Rice straw compost, NPK fertilizer